Implementación de una infraestructura hotelera para el desarrollo de la actividad turística en el balneario Puerto Bajaña cantón Buena Fe año 2019 - Cañarte Mejía, Mishell Selena (2020)
This research project has been carried out to contribute specifically to the tourism sector of the Buena Fe canton, publicizing the services, prices, and types of rooms that the hotel will offer. Let's analyze the influence of the implementation of a hotel infrastructure for the development of tourist activity in the Puerto Bajaña of the Buena Fe canton, in this way the pros and cons of this project can be identified and how to help the tourist part, socioeconomic of the canton. For the execution of this investigative work, information from the field will be collected through observation, structured surveys, interviews, aimed at analyzing the supply and demand of increasing a hotel in the spa, and with the acquired information will be derived to the interpretation of results which helped to conclude that implementing a hotel will increase the influx of tourists and generate jobs helping the development not only tourist but economic of the canton.